ASAS DEMOKRASI EKONOMI DALAM PERBANKAN SYARIAH DI INDONESIA - Rully Trihantana; Muhamad Rizal; Abdul Kodir (SAHID BANKING JOURNAL, 2022)
This research is based on economic democracy and its relationship with Islamic banking. In fact, intermediation encouraged by Islamic banking can create an economic democracy capable of maintaining the continuity of people's lives and existing natural resources, as well as increasing the independence of the nation and state of the Republic of Indonesia. Improvements in the implementation of economic democracy in Islamic banking must continue to be made. The main problem in muamalah Islamic banking is the element of benefit. If there is a problem, then it is very possible that the transaction is allowed. Islamic banking must continue to strive to apply the best practice profit sharing system. Thus there is an optimization of the implementation of the principles of economic democracy through a profit sharing system in musyarakah and mudharabah contracts. Thus, Islamic banking intermediation with profit sharing has become the main type of financing and is the backbone of Islamic banking.